Overtraining the rectus abdominis can make you less efficient in weightlifting - Robinson, E. (Strength and Conditioning Journal, 2010)
Efficient trunk flexion and extension training is paramount to stabilize heavy weights lifted overhead iinw eightlifting. A strong and balanced runk, which includes several muscle groups (not just those superficial muscles that can be seen but perhaps even more importantly the deep ones that hold most of the loads), is necessary for success. This article will discuss the importance of balance between flexion and extension exercises of the trunk, stabilization movements of the trunk, and specific exercises that can be used in a weightlifting training program to most effectively train for stabilization of the weight overhead.